1998
DOI: 10.1146/annurev.soc.24.1.265
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in Organizations and Social Movements: From Hybrid Corn to Poison Pills

Abstract: There has been rapid growth in the study of diffusion across organizations and social movements in recent years, fueled by interest in institutional arguments and in network and dynamic analysis. This research develops a sociologically grounded account of change emphasizing the channels along which practices flow. Our review focuses on characteristic lines of argument, emphasizing the structural and cultural logic of diffusion processes. We argue for closer theoretical attention to why practices diffuse at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
835
3
17

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,294 publications
(873 citation statements)
references
References 91 publications
18
835
3
17
Order By: Relevance
“…Indeed, additional research is needed to understand more fully the "receiving" side of the diffusion process. Using diffusion research (Strang and Soule 1998) as a starting point, researchers can carefully assess how shifts in rationales for adoption influence adoption patterns and identify, at various points in the institutionalization process, whether such adoption is primarily substantive or symbolic.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, additional research is needed to understand more fully the "receiving" side of the diffusion process. Using diffusion research (Strang and Soule 1998) as a starting point, researchers can carefully assess how shifts in rationales for adoption influence adoption patterns and identify, at various points in the institutionalization process, whether such adoption is primarily substantive or symbolic.…”
Section: Resultsmentioning
confidence: 99%
“…Sociologists have studied policy diffusion through the lens of "social construction" since the late 1970s+ 77 Constructivism is rooted in Weber's insight that to understand social action one must grasp its meaning to the actors, and that that meaning is an empirically traceable product of social context+ 78 The distinguishing feature of social constructivism is its focus on the intersubjectivity of meaningboth legitimate ends and appropriate means are considered social constructs+ 79 According to this view, while policymakers believe that they can, should, and do divine the "best practice" in a given policy area, in fact they cannot accurately judge whether policy A is better than policy B with any certainty+ Instead, theory and rhetoric often serve as the basis of decision making+ But theory and rhetoric change over time, and as they do, social meaning is constructed and reconstructed+ Thus, the same policies can have different meanings over time+ Tariffs, for example, were thought to do very different things in 1880, 1947, and 1995+ The "world polity" approach draws on the Weberian view of an increasingly global culture comprising broad consensus on the set of appropriate social actors individuals, organizations, and nation-states have replaced clans, city-states, fiefdoms!, appropriate societal goals~economic growth and social justice have replaced territorial conquest and eternal salvation!, and means for achieving those goals tariff reduction and interest rate manipulation have replaced plunder and incantation!+ Meyer suggested that a view on what is "appropriate"-in terms of actors, goals, and policy means-has diffused from country to country around the globe, first in the West and then elsewhere+ 80 The initial empirical focus was social policies and human rights+ Meyer and colleagues showed that between 1950 and 1970 all countries expanded mass schooling-which had been defined as key to achieving both growth and democracy-regardless of political ideology, political system or level of economic development+ 81 They found that developing and developed countries alike sign human rights treaties to signal their commitment to global norms+ Global norms are strong enough to cause even countries that Amnesty International chides for abusing rights to sign on+ 82 76+ Many researchers find that learning and emulation are not necessarily mutually exclusive+ See, for example, Meseguer 2005+ 77+ The first sustained analysis appeared in Meyer and Hannan 1979+ For reviews of the literature, see Strang and Meyer 1994;Dobbin 1994;Rogers 1995;and Strang and Soule 1998+ 78+ Weber 1978, 4+ 79+ See Hirschman 1977Meyer et al+ 1997;and Berger and Luckmann 1966+ 80+ Boli-Bennett and Meyer 1978+ 81+ See Meyer et al+ 1977andSoysal 1992+ 82+ See Boyle andPreves 2000;Forsythe 1991;and Ramirez and McEneaney 1997+ Social construction became an established paradigm in international relations research in the latter 1990s+ 83 For proponents, u...…”
Section: Emulationmentioning
confidence: 99%
“…Actors that are more centrally located in networks of social relations face greater restrictions on their actions (Davis 1991, Leblebici et al 1991, Strang and Soule 1998. Similarly, organizations with greater visibility are likely to be more limited in their ability to adopt custom-tailored versions, making them more likely to implement versions of a practice that are also adopted by other organizations.…”
Section: Organization-level Mechanisms Affecting Practice Variationmentioning
confidence: 99%